Efektivitas Ekstra Moringa Oleifera Dengan Konsentrasi Dosis Yang Berbeda Terhadap Produksi ASI Ibu Menyusui - Sri Lestari; Arwani Arwani; Irmawati Irmawati (Jurnal Ners, 2025)
The consumption of herbal foods is known to enhance breast milk production in breastfeeding mothers. Therefore, researchers have innovated to improve breast milk production by comparing the administration of Moringa Oleifera extract at various dosages. Objective: The study was to evaluate the effectiveness of Moringa Oleifera extract with different dose concentrations on breast milk production in breastfeeding mothers. Method: This study employed a Kuasi experimental design with a pretest-posttest approach, consisting of three groups. The population included all breastfeeding mothers in the Pagerbarang Health Center Work Area, Tegal Regency, with a sample size of 20 respondents in each group. Interventions involved administering Moringa Oleifera extract at doses of 250 mg, 650 mg, and 800 mg for 14 days. Bivariate analysis was conducted using the Paired Sample T-Test and Wilcoxon test. Results: There was no difference in the increase in breast milk production of breastfeeding mothers based on the category of baby's weight, bowel movements and urination (p> 0.05) after administration of moringa oleifera extract capsules at doses of 250 mg, 650 mg and 800 mg. The dose of 650 was more effective in increasing baby's weight and the dose of 250 was more effective in increasing breast milk production based on the category of baby's bowel movements and urination. Conclusion: The administration of Moringa Oleifera extract capsules at various doses effectively enhances breast milk production in breastfeeding mothers.